Ruang Konselingku: Program Konseling Islami Interaktif Berbasis Media Sosial Sebagai Upaya Mitigasi Stres Akademik Pada Generasi Z - Maulla, Nabilla Fatmawati; Rahmawati, Eka; Fahmi, Lukman (Jurusan Bimbingan dan Konseling Islam, 2024)
Generation Z faces various academic pressures that may lead to stress and have negative impacts on their mental and spiritual health. Generation Z’s close engagement with social media can be utilized as an alternative medium for Islamic counseling services that are more accessible and relevant to their needs. This study aims to examine RuangKonselingku as an interactive Islamic counseling program based on social media, specifically Instagram, designed to help Generation Z mitigate academic stress. This research employs a qualitative approach with a descriptive design through a library research method. Data were obtained from various references, including books, journals, articles, and relevant scientific documents, particularly those published within the last ten years. The data collection instrument was documentation study, while data analysis was conducted using descriptive analysis techniques, including data collection, data reduction, data presentation, and conclusion drawing. The results indicate that RuangKonselingku is an innovative Islamic counseling service with significant potential in providing psychological and spiritual support for Generation Z by utilizing social media as an interactive medium. This program is considered capable of serving as a strategy for mitigating academic stress while strengthening religious values in addressing the challenges of modern education.